Media Dependency During a Food Safety Incident Related to the U.S. Beef Industry - Ashley D. Charanza; Traci L. Naile (Journal of Applied Communications, 2012)
Food safety issues are an important topic in the mainstream media. Media coverage of food safety, particularly the beef industry, has the potential to alter consumers’ perceptions of and attitudes toward the beef industry. Much of the media coverage about food safety incidents related to beef is negative, causing concerns and frustrations among the industry. The media has an important and powerful influence on society; there is a benefit to understanding the role of the media and how people use media in their everyday lives. This study examined consumers’ dependencies on media during normal times when a food safety incident has not occurred or is not expected to occur and during a potential food safety incident in the beef industry. The results showed that consumers use different mediums to receive information during a food safety incident than during normal times. Internet, television news channels, and radio were the top mediums that respondents considered helpful in receiving information related to food safety incidents. Respondents spent more time per week on mediums during normal times than during a food safety incident. Agricultural communicators need to send messages to the mediums consumers use daily to educate the public about food safety issues.
Keywords: media dependency; beef; food safety; U.S. beef industry; agricultural communications; consumers